Tanggung Gugat Penyedia Layanan Terhadap Afiliator Terkait Wanprestasi dalam Perjanjian Afiliasi (Studi Kasus Afiliator Shopee Id: 11377610190) - Laely, Syirtu Fil; Iman, Muh (Indonesian Journal of Law and Justice, 2023)
The rapid development of internet technology influences online shopping activities through e-commerce, especially Shopee which has the Shopee Affiliate program. There are problems that often occur with Shopee Affiliates. One of them is that affiliates do not get full rights to the commission that was agreed upon at the beginning of the agreement. When the commission is not received in accordance with the terms and conditions of the agreement, Shopee can be held accountable. Therefore, this research is focused with the aim of finding out how liable service providers are to affiliates regarding non-performance in affiliate agreements on the Shopee application. The research method used by researchers is a legal research approach, namely legislation (statute approach), cases (case approach), and conceptual approach (conceptual approach) to help obtain data and information needs. In addition, this type of research design involves normative juridical research and is accompanied by the use of library study instruments as an alternative to collecting research supporting materials. Based on the results/findings of research on the problem of affiliate commission cases caused by an element of negligence or deliberate action on the part of Shopee as the organizer and service provider of the Shopee Affiliate program. so in this case, the affiliate of the Shopee Affiliate program who is disadvantaged has the right to file a lawsuit against Shopee who must be held accountable for the breach of contract that has been committed.